Design e-Office Application for Population based on Cloud Computing - Kembuan, Eddy D.R.E; Batmetan, Johan Reimon (JR Education, 2022)
Information and communication technology in the field of population e-office is very useful in supporting the process of data management, information, facts, distribution, and knowledge. The purpose of this research is to build a population e-office application that can produce time, cost and energy effectiveness. This research was developed using an open source-based online administration service administration system method with a cloud computing approach, so that it can be used to collect community data, business permits, recommendations, and administrative handling related to the community in the village. The results of this study indicate that in the existing village administration service system in general, the community and village officials deal with data through applications available for each of these sections separately. The exchange of data between departments, if needed, is still based on paper notes that are delivered from one section to another, it is hoped that this will not happen again with this research. A structured public service administration system architecture can be managed by this system and allows data to be shared in the system.